Online instruction, e-learning, and student satisfaction: A three year study - Michele T. Cole (Athabasca University Press, 2014)
This article presents the results of a three-year study of graduate and undergraduate students’ level of satisfaction with online instruction at one university. The study expands on earlier research into student satisfaction with e-learning. Researchers conducted a series of surveys over eight academic terms. Five hundred and fifty-three students participated in the study. Responses were consistent throughout, although there were some differences noted in the level of student satisfaction with their experience. There were no statistically significant differences in the level of satisfaction based on gender, age, or level of study. Overall, students rated their online instruction as moderately satisfactory, with hybrid or partially online courses rated as somewhat more satisfactory than fully online courses. “Convenience” was the most cited reason for satisfaction. “Lack of interaction” was the most cited reason for dissatisfaction. Preferences for hybrid courses surfaced in the responses to an open-ended question asking what made the experience with online or partially online courses satisfactory or unsatisfactory. This study’s findings support the literature to date and reinforce the significance of student satisfaction to student retention.